Preparação da zeólita ferrierita pelo método de transporte em fase vapor - Modesto Neto, Pedro Paulo (2011)
Ferrierite zeolite has a specific crystalline structure that gives unique catalytic properties that enable the selective isomerization of n-butene to isobutene and selective cracking of n-paraffins in the range of gasoline, mainly producing light olefins (ethylene and propylene). This study focused on assessing the formation and crystal growth method of transport through vapor phase (VTP) for fixed conditions of temperature, Si / Al and time of crystallization. In the work variables were used: structural directors, source of aluminum and % seeds. The experiments showed synthesis for transport method in phase steam with addition of seeds presented satisfactory results. Most of the samples synthesized in the work exhibited high crystalline percentage, with superior values to 90%, when compared with the commercial pattern. The results of crystalline percentage of synthesized materials indicated that there is an outstanding influence of the source of aluminum (sulfate of aluminum or pseudoboehmite) about the crystallization of the ferrierite zeolite for the transport method in vapor phase in the pyrrolidine presence as organic director, however when the director is the ethylenediamine this fact is almost imperceptible.